What do senior genitourinary medicine physicians think of the future of the speciality? A national survey. (October 2021) - Pocock, Mamatha; Kingston, Margaret; Whalley, Simon; Carlin, Elizabeth
Genitourinary Medicine (GUM) is a specialty that has undergone significant change over the past decade. Multiple factors have contributed to this including changes in service models and commissioning landscapes, health service leadership, medical education and changes in the spectrum of our clinical work. The Joint Specialist Committee for GUM at the Royal College of Physicians (RCP) conducted a national survey in December 2019 – January 2020 to understand the changing scope of work for GUM consultants. The survey indicated an increase in clinical complexity alongside a decline in registrar recruitment, staff shortages and service fragmentation. Funding cuts have impacted many services and the majority of consultants feel a return to an NHS commissioning model would be preferable. Despite the many challenges, GUM physicians consider the specialty 'unique, dynamic, friendly and open-minded'. It is clear that senior doctors value the wider clinical, academic and educational opportunities within the specialty.